Physiological profile and activity pattern of young soccer players during match play - Stroyer, J.; Hansen, L.; Klausen, K. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The purpose of this study was to examine aerobic demands and activity patterns during match play in young soccer players with respect to competition level, age, and biological maturity. METHODS: Ten nonelite players (NbP) and nine elite players (EbP) in their early puberty (12 yr), and seven elite players (EeP) in their late puberty (14 yr) were studied. Heart rate (HR) and activity pattern were recorded during match play, whereas corresponding .VO(2) and HR values were obtained during submaximal and maximal treadmill tests in the laboratory. The maturity status was assessed from testicular volume. RESULTS: No difference in .VO(2max) was observed between the nonelite and the elite players in the beginning of puberty (58.7 +/- 5.3 vs 58.6 +/- 5.0 mL O(2).min-1.kg(-1)), whereas the elite players in the end of puberty were significantly more fit (63.7 +/- 8.5 mL O(2).min(-1).kg(-1)). During match play, a higher HR was recorded in the elite players in the beginning of puberty than their nonelite counterparts, whereas the two elite groups showed the same HR responses (HR 1st half/2nd half-NbP: 162/157; EbP: 177/174; EeP: 178/173). The elite players in the end of puberty thus performed a higher absolute and relative .VO(2) (.VO(2).min(-1) and mL O(2).min(-1).kg(-1)) compared with the nonelite players during both halves, corresponding to more time spent in standing/walking in the nonelite group. The elite players in the end of puberty showed higher absolute .V(O2) values during match play than the young elite players but identical relative aerobic loads. It seems that the midfield/attack group had the highest absolute .VO(2max) and was performing at the highest HR during the matches. CONCLUSION: The present study shows that young soccer players are highly specialized both according to playing level and position on the field.